Terminological variation in professional genres: an exploratory study of the teaching guide, the technical report and the judicial ruling - Morgado Fernández, Paula (2026)
Professional discourse has aroused an incipient interest in applied linguistics, especially with regard to the characterization of the genres that circulate within each profession and their teaching in undergraduate programs. However, the study of terminology has received less interest even though it allows us to understand how specialized knowledge is communicated within and outside the professional community. This research explores the terminological variation in the teaching guide, the technical report and the judicial ruling, identifying the rhetorical moves or textual sections where this phenomenon occurs. For this purpose, the base terms and their variants were analyzed in a microcorpus, considering the causes of variation and their semantic distance. The results show terminological variation in the three genres and a predominance of discursive and cognitive causes. The study offers key insights into specialized vocabulary and the perspectives it conveys in Latin American professional contexts.